Persistent Newcastle Disease Virus Infection in Embryonic Chicken Tracheal Organ Cultures - Cummiskey, J. F. (1973)
The persistent infection of embryonic chicken tracheal organ cultures with Newcastle disease virus (NDV) is described. Tracheal explants remained morphologically intact and were able to support the replication of NDV for 6 months. Peak titers of released virus occurred at 1 week postinfection, whereas maximal immunofluorescence was not observed until 30 days postinfection. The inoculum titer was not critical, and viral persistence resulted with either of two strains of NDV tested. Serum was not required in the medium for explant viability or to maintain the persistent infection. The presence of a contaminating virus morphologically resembling a leukovirus neither altered the course of infection nor affected the survivability of explants. Although interferon was not detected in the culture medium, persistently infected explants were resistant to heterologous viral challenge, and a similar resistant state could be induced in uninfected explants with exogenous interferon or ultraviolet light-inactivated NDV. No evidence was found to implicate antibody as a regulatory factor in the establishment or maintenance of persistence. The results from electron microscopy and immunofluorescence suggest the cells of the subepithelial connective tissue as the site of NDV persistence.